Pengaruh Sari Jeruk Siam Pontianak dan Keprok Terigas terhadap Kualitas Es Krim - Trifena Honestin; Imro’ah Ikarini; Hasim Ashari; Zainuri Hanif (xxxx-xxxx, 2020)
Honestin T, Ikarini I, Ashari H, Hanif Z.  2020. Effects of siam pontianak and keprok terigas juice on the quality of ice cream. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Ice cream products made of orange juice may increase the added value of the products. Besides, vitamin C contained in the oranges also contributes to human’s health. The study aims to determine effects of differences in the citrus varieties and the proportion of water compared to orange juice on the overrun value, total dissolved solids, melting rate, vitamin C content, sensory properties of scoring and the panellist’s preference for orange ice cream. The study was designed using Completely Randomized Design with two factors, namely differences in citrus varieties (Siam Pontianak and Keprok Terigas) and the  proportion of orange juice compared to water (1:2; 1:1; 2:1). The results show that the Keprok Terigas ice cream had the highest preference value on the parameters of colour, aroma, taste and texture compared to those of Siam orange ice cream. The highest content of vitamin C was obtained from Siam orange ice cream in the proportion of orange juice compared to water 1:1, vitamin C content was 48.40 mg/100 grams. Total dissolved solids of the orange ice cream ranged from 2.267 – 2.600, pH was between 4.933 – 6.180, the overrun value was between 52.320 – 56.780% and melting rate was between 790.1 - 884.5 seconds. The differences between the Keprok Terigas and Siam Pontianak varieties have affect the value of vitamin C, pH, and overrun. The treatment of the proportion of orange juice: water affected the pH value, total dissolved solids, and overrun, but did not affect the melting rate.